The Effect Of The Legal Adaptation Of The Issue Of Nationality On Issues Of Jurisdiction, How To Prove And Authentic Rulings - جامع, شادي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The Importance Of Nationality Is Defined As A Legal Tool To Distinguish The Patriot From The Foreigner, And It Is Considered The Best Way To Determine The Scope And Extent Of The Rights Enjoyed By The Individual And The Duties That He Has On His Shoulders. Among Those Whom The Latter Addresses (The Individual), The State May Deny The Individual His Enjoyment Of His Nationality, Or Claim That He Is A Member Of His People Against The Reality. Determining The Legal Nature Of Nationality Is It From The General Law Or From The Private Law That Plays A Major Role In Determining The Jurisdiction In Matters Of Nationality. Also, The Method Of Proof Differs When The Subject Of The Conflict Is Linked To The General Law Than It Is In The Provisions Of Private Law, Not To Mention The Authenticity Of The Provisions Also Between The Idea Of ​​Absolute Authenticity And Authenticity Of Relativity. In Our Research, We Will Try To Show The Idea Of ​​Jurisdiction, Evidence And Authenticity Of Rulings In The Matter Of Nationality Through A Comparative Legal Study Between Legal Texts And Jurisprudence And Judicial Rulings.